Pelindungan Data Pribadi Konsumen pada Perusahaan E-commerce yang Mengalami Kepailitan di Indonesia Ditinjau Berdasarkan Hukum Positif Indonesia - Thiara Octaviani Putri; Muhamad Farudin (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid growth of e-commerce has increased the urgency of personal data protection, especially in cases of corporate bankruptcy. Legal uncertainty regarding the status of personal data in bankruptcy assets poses privacy risks. This study examines regulatory gaps in the Bankruptcy and PKPU Law (UU KPKPU) and the Personal Data Protection Law (UU PDP) concerning consumer personal data protection in bankrupt e-commerce companies. This research employs a normative juridical method by analyzing applicable legal norms. This approach reviews legislation, jurisprudence, and other legal documents to understand and evaluate the legal application of personal data protection in e-commerce bankruptcy. The study finds that personal data protection remains a legal obligation for bankrupt e-commerce companies under the UU PDP. However, legal gaps in the UU PDP and UU KPKPU regarding bankruptcy require regulatory harmonization to safeguard consumer privacy rights.